PROJECTS METHOD IN ORGANIZING OF GRAPHICAL TRAINING - Irina D. Stolbova; Evgeniya P. Aleksandrova; Konstantin G. Nosov (Высшее образование в России)
The article discusses the design-targeted approach in higher professional education, especially in subject training. This urgent problem is indicated in the Program of Education Development in the Russian Federation in the years 2016-2020. The authors represent an analysis of innovations that accompany projecting-engineering activity, including using of up-to-date design technologies within the scope of the basic graphical training of students. Thepaper analyzes the possibility of usingthe project method and design technologies in teaching first-and-second-year students. The represented educational technologies have various levels of immersion in the project activities applied in teaching graphical disciplines at Perm National Research Polytechnic University. The need of system and consistent use of project method throughout the subject teaching is discussed. The need of individualization and variation in applied educational procedures is also substantiated.